2004
DOI: 10.1007/s11746-004-966-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of soy protein concentrate and isolate from extruded‐expelled soybean meals

Abstract: Soy protein concentrates (SPC) and soy protein isolates (SPI) were produced from hexane-defatted soy white flakes and from two extruded-expelled (EE) soy protein meals with different degrees of protein denaturation. Processing characteristics, such as yield and protein content, and the key protein functional properties of the products were investigated. Both acid-and alcohol-washed SPC from the two EE meals had higher yields but lower protein contents than that from white flakes. Generally, SPC from an acid wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
81
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 9 publications
8
81
1
4
Order By: Relevance
“…Batal et al (2000) reported that values less than 45% indicate adequate heat treatment of soybeans for chickens. PDI values reported in this study, however, were not as low as those reported to be optimum by Wang et al (2004). This may be because of differences in the source of soybeans used in the two studies.…”
Section: Discussioncontrasting
confidence: 83%
“…Batal et al (2000) reported that values less than 45% indicate adequate heat treatment of soybeans for chickens. PDI values reported in this study, however, were not as low as those reported to be optimum by Wang et al (2004). This may be because of differences in the source of soybeans used in the two studies.…”
Section: Discussioncontrasting
confidence: 83%
“…The hydrolysates either were cooked hydrothermally (jet cooked) in equipment previously described (13) or were spray dried without jet cooking. The U-shaped holding tube of the jet cooker provided 19 s of cooking time at 104°C.…”
Section: Methodsmentioning
confidence: 99%
“…The U-shaped holding tube of the jet cooker provided 19 s of cooking time at 104°C. Jet cooking provides high shear and has been shown to refunctionalize soy flour protein (13), but the purpose of jet cooking in these experiments was to inactivate the enzyme and microorganisms. The slurry was then spray dried in an Anhydro compact spray dryer (APV Crepaco, Inc., Attleboro Falls, MA) using a spinning disk atomizer and 165°C air inlet temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work showed that SPI could be prepared from EE meals; however, the yields were low (the SPI and protein yields were only 25 and 40%, respectively) (6). Inspired by the work of Johnson (3) and Wang and Johnson (4), we demonstrated that hydrothermal cooking (HTC) could be used to refunctionalize heat-denatured proteins of EE meals (5).…”
mentioning
confidence: 97%